Space of Water in Antanas Škema’s Prose - Nagliuvienė, Juldita (Respectus Philologicus, 2001)
If H. Hesse and T. Mann were fascinated by mythology due to its primitive character and its content oriented to complex and the whole embracing creation, Antanas Škėma views mythology as shameless primitiveness, the embodiment of dying lewdness. This is why this writer of exodus deconstructs a myth by creating a new history line in time. Škėma changes an exterior counterpoint, which dominates works of T. Mann, into a comparison of interior high and low sounds, i.e. a correlation of agonizing scream and death. The concept of an archetype, which is becoming extinct, however, which still fatally affects human consciousness, is transmitted into a higher - mystical, perception of visions. Škėmas’ man wrecks a myth to the very sadomasochistic self-destruction for the sake of rebellion as a means for perfection.